Penetrantna keratoplastika pri duševno manj razvitih bolnikih - Pahor, Dušica (Zdravniški vestnik, 2002)
Background. Penetrating keratoplasty (PK) is rarely performed in mentally retarded patients, first of all because of numerous complications after surgery such as inflammation, self-inflicted injury, injury and because of difficult post-operative treatment. The aim of this study was to present the success of PK in this patients. In 16 years (from May 1984 to May 2000) 201 PK were performed, but only three in mentally retarded patients. Methods. We present three cases of PK in mentally retarded patients. All the patients were men. They were 14, 16 and 27 year old. The indication for PK were in two cases acute keratoconus and in one case keratoglobus. The mean follow-up was 24.6 months. Trepanation was made with rotor threpin and donor material was sutured using single continuous 10-0 nylon suture. Results. In two cases keratoplasties stayed clear. Visual acuities were 0,4 and 0,5. In one patient with very aggresive behaviour graft failure developed with significant cornealvascularisation. Re-keratoplasty was not performed. Conclusions. Adequate post-operative care following PK in mentally retarded patients is the most important factor for the success of transplantation. The indication for the surgery must be made very carefully especially in self-aggressive patients in residential care.
Keywords: Cornea; Duševna manjrazvitost; duševno prizadeti; Keratoconus; Keratokonus; Keratoplasty, penetrating; Mental retardation; oftalmologija; Penetrantna keratoplastika; Roženica; therapy; zdravljenje